PROSES REKRUTMEN CALON PERSERTA TUGAS BELAJAR DI LINGKUNGAN PEMERINTAH KKABUPATEN NATUNA - Wan Effendi E.21110110 (FISIP Universitas Tanjungpura, 2013)
Writing this article aims to find out how the process of recruitment of prospective participants in the learning task Natuna regency government. Problems recruiting candidates for study in Natuna regency, there are irregularities in the determination of the prospective participants learned the task. This study used a qualitative approach and a presentation done by descriptive. These results indicate that the recruitment of prospective participants in the process of learning tasks in Natuna regency absence formation requirements planning, rekrutman not based on competence and needs of each SKPD, and the selection is still there is collusion, intervention, and nepotism. Writing articles is also intended, to allow the recruitment of prospective participants learned the task can be accomplished in accordance with the terms and transparent process in its execution, which can lead to prospective participants competence-based learning tasks carried out in an objective, accountable, and in accordance with the needs of the organization. In addition, BKD and Regional Head before determining the formation of necessity there must be a plan needs to be in the recruitment process can be carried out well, as well as a material consideration in making future activities that the employee needs to come. Keywords: Forecasting the needs of prospective employees, recruitment and selection of candidates.